Experimental study of chaotic flow and mixing of Newtonian fluid in a rotating arc-wall mixer. (15th May 2022) - Younes, Eliane; Moguen, Yann; El Omari, Kamal; Burghelea, Teodor; Le Guer, Yves; Castelain, Cathy
Highlights: The novel active inline RAW mixer using chaotic advection is proposed. It is studied experimentally in the case of highly viscous Newtonian fluids. PIV and LIF techniques were used to obtain velocity and concentration fields. Mixing quality was characterized by statistical indicators and FSLE. High mixing efficiency has been achieved and optimal flow conditions were identified. Graphical abstract: Abstract: In order to mix highly viscous fluids with minimal energetic input, a new active in-line mixer has been developed in our previous study (El Omari et al., Phys. Rev. Fluids, 2021 [18]). Based on the principle of mixing by chaotic advection, we present in this paper an experimental characterisation of chaotic mixing of Newtonian fluid flows, at low Reynolds number. First, the flow is characterized using velocity field measurements. Distinct flow topologies are detected in the flow. The trajectories of the fluid particles are computed and show the generation of complex structures in the flow. Residence time distributions reveal that the fluid particles spend more time in the mixer under favorable controlling conditions. Finite size Lyapunov exponents are calculated and indicate that the flow is more chaotic for these conditions. Next, the mixing patterns are visualized and showed that the mixing is more homogeneous under the same favorable conditions for which the fluid particles are sufficiently subjected to the stretching and folding mechanism.